2016
DOI: 10.1002/ase.1591
|View full text |Cite
|
Sign up to set email alerts
|

A practical hybrid model of application, integration, and competencies at interactive table conferences in histology (ITCH)

Abstract: Significant changes have been implemented in the way undergraduate medical education is structured. One of the challenges for component courses such as histology in medical and dental curricula is to restructure and deliver training within new frameworks. This article describes the process of aligning the purpose and experience in histology laboratory to the goal of applying knowledge gained to team-based medical practice at Tulane University School of Medicine. Between 2011 and 2015, 711 medical students took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In the previous survey, only 64% of the respondents indicated that their course was part of an integrated curriculum, compared with 98% in the current survey. This finding is supported by an increasing number of reports on the integration of microscopic anatomy into organ system‐based curriculum (Ettarh, ).…”
Section: Discussionsupporting
confidence: 54%
“…In the previous survey, only 64% of the respondents indicated that their course was part of an integrated curriculum, compared with 98% in the current survey. This finding is supported by an increasing number of reports on the integration of microscopic anatomy into organ system‐based curriculum (Ettarh, ).…”
Section: Discussionsupporting
confidence: 54%
“…Active learning in small groups was also beneficial in accommodating different student learning styles, providing students with an opportunity to think, discuss, and process module‐related topics as well as develop a stronger sense of teamwork, collaboration, and community. Active, group‐based learning in histology laboratories has been described previously (Bloodgood, ; Shaw and Friedman, ; Sahota et al, ) and shown to enhance performance in examinations (Ettarh, ). Importantly, current virtual microscopy viewer software allows sharing of annotated images between students and permits group learning (Sander and Golas, ).…”
Section: Discussionmentioning
confidence: 99%
“…group-based learning in histology laboratories has been described previously (Bloodgood, 2012;Shaw and Friedman, 2012;Sahota et al, 2016) and shown to enhance performance in examinations (Ettarh, 2016). Importantly, current virtual microscopy viewer software allows sharing of annotated images between students and permits group learning (Sander and Golas, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At another medical school, a histology course uses clinical correlation within lectures to demonstrate how histology is related to disease and pathological conditions. 3 …”
Section: Classification Of Clinical Correlationsmentioning
confidence: 99%
“…For example, they can be very superficial, such as the relationship of histology to a disease condition during a didactic lecture. 3 Alternatively, they can involve deeper active-learning experiences such as concept mapping 4 or the use of patient simulator exercises. 5 Clinical correlations can be used to show that the basic science concepts being taught are relevant to medicine and thus of practical use, without requiring a student to learn details about a disease or its clinical treatment.…”
Section: Introductionmentioning
confidence: 99%